Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

How can I find the sum of the infinite series $$\frac{1}{5} - \frac{1\cdot4}{5\cdot10} + \frac{1\cdot4\cdot7}{5\cdot10\cdot15} - \cdots\qquad ?$$

My attempt at a solution - I saw that I could rewrite it as $$\frac{1}{5}\left(1 - \frac{4}{10} \left( 1 - \frac{7}{15} \left(\cdots \left(1 - \frac{3k - 2}{5k}\left( \cdots \right)\right)\right.\right.\right.$$ and that $\frac{3k - 2}{5k} \to \frac{3}{5}$ as $k$ grows larger. Using this I thought it might converge to $\frac{1}{8}$, but I was wrong, the initial terms deviate significantly from $\frac{3}{5}$.

According to Wolfram Alpha it converges to $1-\frac{\sqrt[3]{5}}{2}$. How can I get that ?

share|cite|improve this question
up vote 22 down vote accepted

\begin{align*}(-1)^{n-1}\frac{1\cdot 4 \dots (3n-2)}{5\cdot 10 \dots 5n}&= (-1)^{n-1}\frac{3^n}{5^n}(-1)^n\frac{(-\frac{1}{3})\cdot (-\frac{4}{3}) \dots (-\frac{3n-2}{3})}{1\cdot 2 \dots n}\\ &= -(3/5)^n\binom{-1/3}{n}\end{align*}

Therefore, you can obtain

$$\sum_{n=1}^{\infty} -(3/5)^n\binom{-1/3}{n} = 1 - \sum_{n=0}^{\infty} (3/5)^n\binom{-1/3}{n} = 1- (1+\frac35)^{-1/3} = 1- \sqrt[3]{5/8} =1-\frac{\sqrt[3]5}{2}$$

share|cite|improve this answer

Here is a way that uses the Gamma function, and that was strangely the first thing to come to mind. (Warning!: It is perhaps more complicated than necessary.)

Let $I$ denote your infinite series. We can write this as $$I=\sum_{n=0}^{\infty}(-1)^{n}\prod_{m=0}^{n}\frac{3m+1}{5m+5}$$ which becomes

Now since $$\Gamma\left(\frac{1}{3}\right)\prod_{m=0}^{n}\left(m+\frac{1}{3}\right)=\Gamma\left(n+\frac{4}{3}\right)$$ we have $$I=\frac{1}{\Gamma\left(1/3\right)}\sum_{n=0}^{\infty}(-1)^{n}\frac{3^{n+1}}{5^{n+1}(n+1)!}\Gamma\left(n+\frac{4}{3}\right).$$ By the definition of $\Gamma(s)$ we have $$\Gamma\left(n+\frac{4}{3}\right)=\int_{0}^{\infty}t^{n+\frac{1}{3}}e^{-t}dt,$$ which implies that $$I=\frac{1}{\Gamma\left(1/3\right)}\int_{0}^{\infty}t^{-\frac{2}{3}}e^{-t}\sum_{n=0}^{\infty}(-1)^{n}\frac{3^{n+1}t^{n+1}}{5^{n+1}(n+1)!}dt$$ by switching the order of summation and integration. As $$1-\sum_{n=0}^{\infty}(-1)^{n}\frac{3^{n+1}t^{n+1}}{5^{n+1}(n+1)!}=\sum_{n=0}^{\infty}(-1)^{n}\frac{3^{n}t^{n}}{5^{n}n!}=e^{-\frac{3t}{5}}$$ it follows that $$I=\frac{1}{\Gamma\left(1/3\right)}\int_{0}^{\infty}t^{-\frac{2}{3}}e^{-t}\left(1-e^{-\frac{3t}{5}}\right)dt=1-\frac{1}{\Gamma\left(1/3\right)}\int_{0}^{\infty}t^{-\frac{2}{3}}e^{-\frac{8}{5}t}dt$$ Setting $u=\frac{8}{5}t$ we get $$\frac{1}{\Gamma\left(1/3\right)}\int_{0}^{\infty}t^{-\frac{2}{3}}e^{-\frac{8}{5}t}dt=\frac{1}{\Gamma\left(1/3\right)}\left(\frac{5}{8}\right)^{\frac{1}{3}}\int_{0}^{\infty}u^{-\frac{2}{3}}e^{-u}du=\frac{\left(5\right)^{\frac{1}{3}}}{2}$$and hence $$I=1-\frac{\left(5\right)^{\frac{1}{3}}}{2}$$ as desired.

I hope that helps,

share|cite|improve this answer
This is so complicated. – user9413 Apr 24 '11 at 2:30
@Chandru: There is already a simpler solution. Eric's example is still quite interesting and there's a lot to learn from it. – Jacob Apr 24 '11 at 2:47
Of course no problem is permitted with a complicated solution! – GEdgar Jun 17 '11 at 17:52

You use this formula $$(1+x)^{-p/q} = 1 - \frac{\displaystyle\frac{p}{q}}{1!}\cdot x + \frac{ \displaystyle\frac{p}{q} \cdot \Bigl(\frac{p}{q}+1\Bigr)}{2!} x^{2} - \cdots$$

So your series can be rewritten as $$ \frac{1}{3} \times \frac{3}{5} - \frac{\displaystyle\frac{1}{3}\cdot\Bigl(\frac{1}{3} + 1\Bigr)}{2!} \times \Bigl(\frac{3}{5}\Bigr)^{2} + \frac{\displaystyle\frac{1}{3} \cdot \Bigl(\frac{1}{3}+1\Bigr) \cdot \Bigl(\frac{1}{3}+2\Bigr)}{3!} \times \Bigl(\frac{3}{5}\Bigr)^{3} - \cdots$$

So this is nothing but $$\Bigl(1+\frac{3}{5}\Bigr)^{-1/3} -1 = \frac{1}{3} \times \frac{3}{5} - \frac{\displaystyle\frac{1}{3}\cdot\Bigl(\frac{1}{3} + 1\Bigr)}{2!} \times \Bigl(\frac{3}{5}\Bigr)^{2} + \cdots$$

So our answer will be $$1 - \Bigl(\frac{8}{5}\Bigr)^{-1/3} = 1 -\frac{5^{1/3}}{2}$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.